Diet of three sympatric Physalaemus (Anura: Leptodactylidae) from the Brazilian semiarid region - de Oliveira, Cicero Ricardo; Cavalcante, Leonides Azevedo; Machado, Heitor Tavares de Sousa; Ávila, Robson Waldemar; Morais, Drausio Honorio (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2021)
Studies on the use of food resources and trophic niche of different species can help understand ecological relationships. In this study, we evaluated the diet of three sympatric species of Physalaemus from the Brazilian semiarid. We analyzed a total of 264 individuals, being 100 specimens of Physalaemus albifrons, 93 of P. cicada, and 71 of P. cuvieri. Seven prey categories were recorded: three for P. cicada and P. albifrons, and six distinct categories for P. cuvieri. The orders Coleoptera, Isoptera and the family Formicidae were the most representative categories in the diet of P. cicada, P. cuvieri, and P. albifrons, respectively. Although there is a high trophic niche overlap, differences in preference for food categories may reduce potential competition in these frog species from the Caatinga.